Unlocking the therapeutic potential of microalgal astaxanthin a super antioxidant in oral cancer and associated ailments - Ashokkumar Veeramuthu (Oral Oncology Reports)
Emerging evidence highlights that algal carotenoids, especially astaxanthin, as potent allies in promoting oral well-being. These carotenoids are rich in microalgae and some selected seafoods. Astaxanthin a super carotenoid boasts robust antioxidant, anti-inflammatory, and anti-cancer properties, offering hope in oral cancer management. It neutralizes harmful free radicals, shields against oxidative stress, and collaborates with the body's own antioxidants. These carotenoids directly target the oral cancer cells, triggering their programmed death, restraining proliferation, and hindering tumor advancement. In addition, carotenoids also enhances the effectiveness of traditional cancer treatments while minimizing their harm to healthy tissues. Studies show that astaxanthin exhibits promise in addressing periodontal ailments, oral mucositis, and potentially pre-cancerous conditions, showcasing its versatility in oral health care. Therefore, future research should aim at refining dosage strategies, investigating delivery mechanisms, and executing comprehensive clinical trials to validate its efficacy. Astaxanthin emerges as a game-changer in oral health, poised to enhance outcomes and alleviate suffering in oral diseases.